Implementation Of Vaccination Policy In Cirapuhan Village Selaawi District Garut Regency - Dwi Nurhayati; Adi Sugardi (Fakultas Ilmu Sosial dan Ilmu Politik - Universitas Garut, 2023)
Vaccination in Cirapuhan Village, Selaawi District, Garut Regency is still not evenly distributed so it can hinder the realization of herd immunity in the context of the Covid-19 pandemic. In this study, researchers used a qualitative method with a descriptive approach with secondary and primary data sources. The results showed the implementation of the Garut Regent's Decree No. 443.2/KEP.1103.DINKES/202 The village task force always coordinated through the group social media, socialized, and mobilized the community of the Cirapuhan Village Covid-19 task force. However, the implementation of Garut Regent Decree No. 443.2/KEP.1103.DINKES/202 to achieve herd immunity has not been realized optimally because some people refuse to be vaccinated for fear of side effects and there is an assumption that people do not need vaccination. Based on the results, it can be concluded that the implementation of the Garut Regent's Decree Number 443.2/KEP.1103.DINKES/202 in Cirapuhan Village is still not optimal for the realization of Herd Immunity because the vaccination target in Cirapuhan Village is still many people who refuse to be vaccinated.